Microaggressions and Implicit Bias in Surgical Training: An Undocumented but Pervasive Phenomenon. Issue 1 (9th January 2023) - Alimi, Yewande; Bevilacqua, Lisa A.; Snyder, Rebecca A.; Walsh, Danielle; Jackson, Patrick G.; DeMaria, Eric J.; Tuttle, Janet E.; Altieri, Maria S.
Abstract : Objective: To examine the prevalence, nature, and source of microaggressions experienced by surgical residents during training. Summary and Background Data: The role of microaggressions in contributing to workplace culture, individual performance, and professional satisfaction has become an increasingly studied topic across various fields. Little is known about the prevalence and impact of microaggressions during surgical training. Methods: A 46-item survey distributed to current surgical residents in training programs across the United States via the Association of Program Directors in Surgery listserv and social media platforms between January and May 2020. Survey questions explored the frequency and extent of events of experiencing, witnessing, and responding to microaggressions in the workplace. The primary outcome was the occurrence of microaggressions experienced by surgical residents. Secondary outcomes included the nature, impact, and responses to these events. Results: A total of 1624 responses were collected, with an equal distribution by self-identified gender (female, n = 815; male, n = 809). The majority of trainees considered themselves heterosexual (n = 1490, 91.7%) and White (n = 1131, 69.6%). A majority (72.2%, n = 1173) of respondents reported experiencing microaggressions, most commonly from patients (64.1%), followed by staff (57.5%), faculty (45.3%), and co-residents (38.8%). Only a small proportion (n = 109, 7.0%) of residents reported these events to graduate medical education office/program director. Nearly one third (30.8%) of residents said they experienced retaliation due to reporting of micro-aggressions. Conclusions: Based on this large, national survey of general surgery and surgical subspecialty trainees, microaggressions appear to be pervasive in surgical training. Microaggressions are rarely reported to program leadership, and when reported, can result in retaliation.